Sleep quality and well-being in relation to caffeine consumption among adolescents in Iceland - Júlía Kristine Jónasdóttir 1998- (2022)
Sleep is beneficial to physical and mental health and sleep deprivation has been linked to several health-related issues and mental diseases in adolescence. Caffeine use is common among young people, and it is frequently utilized as a fast remedy for exhaustion. Caffeine is the most commonly ingested stimulant in the world and studies suggest that caffeine improves alertness and lowers tiredness in most people. However, caffeine has also been linked to headaches, stress, anxiety, increased vascular resistance, and it can have a detrimental impact on sleep quality. Therefore, the study’s aim was to examine if adolescents’ caffeine consumption was associated with well-being and sleep quality. A questionnaire was used to measure caffeine consumption, sleep quality, anxiety, depression, and stress in a sample of 150, 16 years old high school students. Almost half of the participants drank caffeinated beverages moderately or often and most of them had good sleep quality. The results showed an association between caffeine consumption and sleep quality, higher caffeine consumption leads to worse sleep quality. These results can be used to educate adolescents about the negative consequences of high caffeine use and poor sleep quality. Further research is needed on the implications of caffeine consumption among adolescents. Keywords: adolescents, caffeine consumption, sleep quality, anxiety, depression, stress, well-being Svefn er mikilvægur fyrir bæði líkamlega og andlega heilsu og svefnskortur hefur neikvæð áhrif á ýmsa heilsutengda þætti og geðraskanir hjá unglingum. Koffínneysla er algeng meðal ungs fólks og er koffín oft notað sem skyndilausn við þreytu. Koffín er algengasta örvandi efni í heiminum og benda rannsóknir til að koffín bæti árvekni og dragi úr þreytu hjá flestum. Aftur á móti hefur koffín líka verið tengt við höfuðverk, streitu, kvíða, háan blóðþrýsting og koffín getur að auki haft skaðleg áhrif á svefngæði. Markmið rannsóknarinnar var að kanna hvort koffínneysla ungmenna tengdist vellíðan þeirra og ...